Enhancing Financial Sector Surveillance in Low-Income Countries : Background Paper. (Policy Papers; Policy Paper ;, 2012)
This note provides an overview of the literature on the challenges posed by shallow financial systems for macroeconomic policy implementation. Countries with shallow markets are more likely to choose fixed exchange rates, less likely to use indirect measures as instruments of monetary policy, and to implement effective counter-cyclical fiscal policies. But causation appears to work in both directions, as policy stances can themselves affect financial development. Drawing on recent FSAP reports, the note also shows that shallow financial markets tend to increase foreign exchange, liquidity management, and concentration risks, posing risks for financial stabilitya.